Effect of Photosynthetic Pigment Composition of Tropical Marine Microalgae from Ambon Bay Navicula sp. TAD on Dye-Sensitized Solar Cell Efficiency - Ivon Telussa; Eirene G. Fransina; Eka Rahmat Mahayani Anthonio Putera Lilipaly; Alfa Musa Imanuel Efruan (Science and Technology Indonesia, 2022)
Solar cells using dyes as sensitizers continue to expand. The synthetic dye used as a sensitizing material for solar cells has high production costs, difficult to find, and can cause environmental pollution. Photosynthetic pigments as sensitizers are considered to be the solution to this matter. In this research, we investigated the effect of photosynthetic pigments from the Navicula sp. TAD as a dye-sensitized material on the efficiency of Dye-Sensitized Solar Cell. To obtain high biomass, the Navicula sp. TAD was cultivated in a modified medium. Pigment extract from dry biomass using acetone, then continued with purification of the pigment using column chromatography techniques. Characterization of pigment by scanning the absorption pattern of visible rays, the fabrication of solar cells with TiO2 paste, and the photographic test of the solar cells filled with solar simulators. Navicula sp. TAD has photosynthetic pigments consisting of chlorophyll and carotenoid with 8.570 gmL−1 and 2.581 gmL−1, respectively. Solar cells using pigment crude extract, chlorophyll, and xanthophyll which TiO2 absorbs as electrodes, have efficiency values of 6.150×10−4, 3.482×10−3, and 4.117×10−3%, respectively.